Integrasi dan Pengelolaan Kebun Komunitas dalam Pembangunan Kota: Belajar dari Kebun Komunitas di Nantes, Perancis - Kurnianingtyas, Agnesia Putri (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Urban densification due to population growth and urbanization could reduce the availability of green spaces and degrade the environment in the city. To overcome this problem and to be able to create a sustainable urban development, the city needs to work harder. An alternative solution that can be used is to develop garden community, as is done in Nantes, France. This study is done to search the integration and the management of the garden community in Nantes, France. The aim of this study is to search best practice of the garden community in Nantes as a comparison to develop the garden community in Indonesia, especially the history and evolution of the garden, the characteristic, the regulation and policy, the actors, the process of development and management, and also the role and challenge of the development and management of the garden community. The approach of this study is the qualitative approach and the analyses methods of analysis is qualitative descriptive. From this study, we can see that the choice of the municipality to intervene more in the technical level and ensure a significant opportunity for residents and the association to develop and run their garden, allowed the municipality to be able to control the development of the gardens without restrict the resident’s chance to participate as actors of development.